SEJARAH PERJUANGAN BUYA AHMAD YUSUFAL-HAJJ DI KABUPATEN INDRAGIRI HULU TAHUN 1945-1950 - Polikasari, Natasya; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Buya Ahmad Yusuf Al-Hajj is one of the fighters in maintaining and filling independence in Riau province. Buya Ahmad Yusuf Al-Hajj plays an important role in maintaining independence in Riau Province. The research is to find out the life history of Buya Ahmad Yusuf Al-Hajj, to find out the history of the struggle in the colonial era, the results of this study are the many contributions Buya Ahmad Yusuf Al-Hajj made during his lifetime . During the Dutch colonial period, as Defense Army of the Motherland (PETA), he was put in charge of the Indonesian armed forces and the youth struggle. When the Dutch Aggression II executed guerrillas with the people and joined the South Riau Guerilla Base Command XI. After the end of the Dutch Aggression II, many of Buya Ahmad Yusuf Al-Hajj's contributions to promoting independence included the chairman of the Indragiri Regency Cooperative Education Center, the head of the Consumption Cooperative Center in Rengat, the head of the Office of the Information Department of Indragiri Hulu Regency and Indragiri Hilir. The method used in this research is a historical research method that consists of four phases, namely heuristic, source criticism, interpretation and historiography. Data obtained from the interviews supplemented with data obtained from books and archives. Data obtained from interviews and literature studies are then analyzed in their own language. The place of research in writing this scientific article is in Airmolek. The techniques used are documentation, interviews and related literature in the history of Buya Ahmad Yusuf Al-Hajj's struggle in Indragiri Hulu Regency.Key Words: Ahmad Yusuf Al-Hajj, the Indragiri Regency